Formulation and Evaluation of Kaptopril Tablets Using Threaded Amylum Tubes and HPMC as Fillers and Binders of the Direct Method - Ahmad Sastra Kelana; Aris Perdana Kusuma; Oktavia Indrati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Indonesia is a tropical country which has many potential plants as excipients, likestarches and tubers. Amylum of taro tuber (Colocasia esculenta) has the potential to be developed into excipient but its use is limited. The purpose of this study was to optimize the formulation and to evaluate the characteristics of captopril tablets by using amylum of taro tuber and HPMC modified as filler and binder on direct compression method. Amylum of taro tuber was obtained by extraction process, then combined with HPMC by partial pregelatination and co-process method. Variation of the starch was divided into five formulation. The main test included friability test, hardness test, dissolution test, and assay. The data analysis was done by theoretical approach between the evaluation result and the literature to observe the result of the modification formulation. It indicated that the combination of equal amount of taro amylum and microcrystalline cellulose (MCC) pH 102 (50% : 50%) has the best result among others. Friability percentage was 0.17 ± 0.07%, disintegration time was 12.09 ± 0.52 minutes, assay was 97.88 ± 1.71% and dissolution test results was 90.65 ± 4.81%.